Análisis del comportamiento del consumo con dinero plástico en la ciudad de Guayaquil - Quimí Meza, María Gabriela (2023)
In current times it is less and less practical to use cash, and consequently, the increasing use of plastic money, particularly credit or debit cards through which it is possible to carry out all kinds of transactions with notorious comfort. These advances of course are accompanied by the monitoring of their effective behavior, hence the research results presented in this report have originated on the basis of the questioning about the regularity of payments with plastic money in the city of Guayaquil, which led to raise the objective of analyzing the behavior of consumption of transactions with plastic money specifically with credit card, in that city. The research process carried out followed a methodology of mixed approach and descriptive type, with the application of techniques such as the survey of cardholders in Guayaquil and also the interview aimed at specialists in the financial system. The results obtained indicate the effective use of credit cards mostly by young people aged 30 to 40 years given the economic stability that generally prevails at that stage of people's lives; But it was also evident the trend of acceptance in the use of this form of payment as well as the need to consolidate an education aimed at financial culture in the general population for the enjoyment with economic discipline of this technological advance.